Assessment of the affective and rational bases for urgent decision-making under extreme circumstances - Cosentino, Alejandro César (2017)
In the framework of dual-type theories, decision making is based on two types of information processing: intuitive and rational. Inspired by this framework, our aims were to develop a brief selfrating measurement instrument to assess the affective and rational bases for urgent decision-making under extreme circumstances, and to study its psychometric properties. The samples comprised cadets from a military academy and participants from the general population. The results showed evidence of acceptable reliability as well as structural, convergent, and discriminant validity for the Bases for Urgent Decisions under Extreme Circumstances Inventory (BUDECI), the new 8-item inventory.